2014
DOI: 10.4314/gjds.v9i2.3
|View full text |Cite
|
Sign up to set email alerts
|

When Empowerment Disempowers: A case study of Ghana’s Community- Based Rural Development Projects

Abstract: This paper argues that the term 'empowerment' is too complex a concept to be simply 'inserted' into development project designs without prior and precise conceptualization. Drawing on qualitative research conducted in 2010/2011 and using Ghana's Community-Based Rural Development Projects (CBRDP) as a case study, the paper outlines power struggles that occurred between Traditional Chiefs and Local Government Officials over the right to manage the projects. The analysis shows that the mal-application of 'empower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…This study agrees with Guri (2006) that traditional leaders provide an opportunity for Ghana to become a unique example of a decentralization model which combines formal and traditional governance systems. A few studies have shown that DAs will not be very successful if they do not work in collaboration with traditional authorities (Adusei-Asante and Hancock, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study agrees with Guri (2006) that traditional leaders provide an opportunity for Ghana to become a unique example of a decentralization model which combines formal and traditional governance systems. A few studies have shown that DAs will not be very successful if they do not work in collaboration with traditional authorities (Adusei-Asante and Hancock, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, participants expressed concern about the elimination of Chiefs from the current decentralization system completely as it would affect the working relations between Chiefs and local government actors. Studies show that it will be difficult for DAs to be very successful if they do not collaborate with traditional authorities (Adusei- Asante and Hancock, 2012). This is reiterated in one Chief's remarks:…”
Section: The Role Of Chiefs In the Communitiesmentioning
confidence: 99%
“…Moreover, the disposition to treat government funds as gifts reflects an entitlement mentality. According to Azarya and Chazan (2018) and Adusei‐Asante (2013), the dependence mindset in Ghana aligned with the country's colonial past and post‐independence socialist experiences. The authors argued that the system of Indirect Rule presented governments as external entities that clandestinely robbed citizens of what rightly belonged to them, and the socialist era represented the return of citizens' share of the national cake deprived them.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of representation is partly due to the diverse interpretations of leadership (Honyenuga and Wutoh, 2019) and the perception that traditional leadership cannot be fused with democratic institutions (Boateng and Afranie, 2020a;Beall et al, 2005). The neglect and its subsequent disempowerment have created tensions among development stakeholders regarding the management of educational facilities (Adusei-Asante and Hancock, 2012). Effective collaboration and clarification of roles are essential in managing such tensions (Boateng and Bawole, 2021;Boateng and Afranie, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…, 2005). The neglect and its subsequent disempowerment have created tensions among development stakeholders regarding the management of educational facilities (Adusei-Asante and Hancock, 2012). Effective collaboration and clarification of roles are essential in managing such tensions (Boateng and Bawole, 2021; Boateng and Afranie, 2020b).…”
Section: Introductionmentioning
confidence: 99%